Response of oil palm to Ganoderma boninense, Trichoderma harzianum and Glomus etunicatum interactions - Alizadeh, Fahimeh (2012)
Knowledge on the microbial relationship and molecular mechanism during oil palmfungi interactions is of primary importance for the development of diagnostic tools for early detection of basal stem rot disease caused by Ganoderma species. Mycelial growth rate of different Ganoderma species were examined on various culture media to develop a medium for rapid growth of Ganoderma species. Rubber or oil palm wood waste was sufficient to improve growth of Ganoderma species; hence could be a useful renewable source for the early detection of Ganoderma disease. The density of soil microfungal community and growth profile of oil palm seedlings were investigated in oil palm artificially inoculated with pathogenic fungus Ganoderma boninense and the symbiotic fungi Trichoderma harzianum and Glomus etunicatum. Densities of the soil microfungal community increased significantly in oil palm inoculated with T. harzianum and G. etunicatum, while oil palm inoculated with G. boninense showed a significant decrease in the density of the soil microfungal community. Thus, the density of soil microfungal community could be useful for early detection and control of Ganoderma disease in oil palm. Fatty acid (FA) signaling is emerging as an important mechanism in plant response during interaction with microbial organisms. Furthermore plants have several antioxidant scavenging mechanisms which are induced in response to biotic and abiotic stresses. For a comprehensive evaluation of key genes involved in FA pathway and antioxidant reactive oxygen species (ROS) scavenger genes during oil palm-G boninense and -T. harzianum interactions, a lane-based array analysis of gene expression in artificially inoculated oil palm seedlings was performed. The results obtained demonstrated that acetyl-CoA carboxylase, β-ketoacyl-ACP synthases II and III, Δ9-stearoyl-acyl carrier protein desaturase, palmitoyl-ACP thioesterase, oleoyl-ACP thioesterase and glycerol-3-phosphate acyltransferase showed identical response in root and leaf tissues for the same fungi. Oil palm-G. boninense interaction up-regulated the expression of these genes in both root and leaf tissues and induced plant defense responses at 21 days postinoculation (dpi). Thereafter the production of physical symptoms occurred at 42 and 63 dpi concomitantly with suppression of expression of these genes. In oil palm-T. harzianium interaction increase in the expression level of these genes was observed in both tissues which correlated with the colonization of roots and promotion of plant growth at 3-63 dpi. The results from transcript level analysis of antioxidant ROS scavenger genes, metallothionein type 3 (MT3-A and MT3-B) revealed a different pattern of gene expression. Expression of MT3-A in roots was significantly up-regulated in G. boninense inoculated seedlings at 21 dpi. While the transcripts of MT3-A and MT3-B genes were synthesized in G. boninense inoculated leaves at 42 dpi, and the analyses did not show detectable expression of these genes before 42 dpi. In T. harzianum inoculated seedlings, the MT3-A expression was significantly up-regulated in roots at 3 dpi and thereafter were maintained at this level. The expression levels of MT3-A and MT3-B were induced in leaves at 3 dpi and subsequently maintained at same levels until 63 dpi. Differences in the expression profiles of the FA biosynthetic pathway genes during pathogenic and symbiotic interaction demonstrated their role in plant resistance mechanism and growth promotion by T. harzianum and could be the basis for molecular marker development for early detection of infection. The antioxidant ROS scavenger genes expressed in leaves and root tissues during oil palmfungi interactions led to the discovery of their potential use as marker for the detection of oxidative stress.